Repeated exposure decreases aesthetic chills likelihood but increases intensity. - Felix Alexandre Schoeller; Leonardo Christov-Moore; Caitlin Lynch; Abhinandan Jain; Thomas Diot; Nicco Reggente (PLoS ONE)
Aesthetic chills are a peak emotional response to stimuli such as music, films, or speech characterized by shivers and goosebumps and activation of dopaminergic circuits. Despite growing scientific interest in this phenomenon, repeated exposure to chills stimuli has not been studied yet, due to the absence of a validated database. This study leverages a recent gold standard in chills stimuli to investigate the impact of repeated exposure on the frequency and intensity of aesthetic chills. Participants (n = 58) were randomly exposed to 6 chill-evoking stimuli pre-validated on the population of interest, in a counterbalanced order. Our findings revealed a significant decrease in the likelihood of experiencing chills with repeated exposure, suggesting habituation to chills itself or potential fatigue in response to aesthetic stimuli. However, we observed an increase in the intensity and duration of chills over successive exposures among those who did experience chills. The study also identified distinct demographic and psychophysiological response patterns across different participant groups, indicating variability in chill responses. These results provide insights into the dynamic nature of aesthetic experiences and their underlying neural mechanisms, with implications for understanding emotional and reward processing in psychophysiology.